Data Visualization of the Number of Foreign And Domestic Tourist Visits to East Nusa Tenggara Using Google Data Studio - Desy Misnawati; Tobias Duha; Ade Risna Sari; Gamar Al Haddar; Iwan Henri Kusnadi (Sean Institute, 2022)
Data presentation techniques are critical in the development of information technology for processing data and producing information. One of the factors to consider while making judgments is the process of converting data into information. Google Data Studio can be used to turn data into information about changes in a data variable over a specific time period. This visual data can be examined and shown in the form of visual graphs and diagrams, for example, data on tourist and foreign visits to an area. This study includes data on local and foreign tourist visits to East Nusa Tenggara in terms of the number of tourists staying at Bintang Hotels from 2019 to 2022. According to the study's findings, the number of tourists visiting star hotels increased and decreased dramatically between 2019 and 2022. In 2019, for example, the largest number of domestic guests was 375,506 people, while the highest number of overseas guests was 43,094 people. Domestic visitors visited 221,884 persons in 2020, while overseas visitors visited 8,420 people. Domestic visitors will increase slightly to 322,024 in 2021, while overseas visitors will fall to 6,095 in 2021. There were 115,839 local guests and 3,201 overseas guests from 2022 to April.